Connected correlator of 1/2 BPS Wilson loops in N = 4 $$ \mathcal{N}=4 $$ SYM - Kazumi Okuyama (Journal of High Energy Physics, 2018)
Abstract We study the connected correlator of 1/2 BPS winding Wilson loops in N = 4 $$ \mathcal{N}=4 $$ U(N) super Yang-Mills theory, where those Wilson loops are on top of each other along the same circle. We find the exact finite N expression of the connected correlator of such Wilson loops. We show that the 1/N expansion of this exact result is reproduced from the topological recursion of Gaussian matrix model. We also study the exact finite N expression of the generating function of 1/2 BPS Wilson loops in the symmetric representation.